New Species of Exomalopsis and Its Associated Cleptoparasite Nomada from Colombia with Description of the Nest (Hymenoptera: Apoidea: Anthophila: Apidae). (14th March 2013) - Velez-Ruiz, Rita I.; Smith-Pardo, Allan H.
Abstract : We describe two new species of bees from Colombia; one is a species of Exomalopsis found nesting in the city of Medellin, Colombia, (the host) and its cleptoparasitic bee, a species of the genus Nomada . In addition, we provide information on the nest architecture of the new species and provide data on occupancy by both the host bee and its cleptoparasite. We present an updated list of the species of Exomalopsis and Nomada of Colombia and taxonomic keys to the species of Exomalopsis.